Botulinum neurotoxin type A: Actions beyond SNAP-25?. (1st September 2015) - Matak, Ivica; Lacković, Zdravko
Abstract: Botulinum neurotoxin type A (BoNT/A), the most potent toxin known in nature which causes botulism, is a commonly used therapeutic protein. It prevents synaptic vesicle neuroexocytosis by proteolytic cleavage of synaptosomal-associated protein of 25 kDa (SNAP-25). It is widely believed that BoNT/A therapeutic or toxic actions are exclusively mediated by SNAP-25 cleavage. On the other hand, in vitro and in vivo findings suggest that several BoNT/A actions related to neuroexocytosis, cell cycle and apoptosis, neuritogenesis and gene expression are not necessarily mediated by this widely accepted mechanism of action. In present review we summarize the literature evidence which point to the existence of unknown BoNT/A molecular target(s) and modulation of unknown signaling pathways. The effects of BoNT/A apparently independent of SNAP-25 occur at similar doses/concentrations known to induce SNAP-25 cleavage and prevention of neurotransmitter release. Accordingly, these effects might be pharmacologically significant. Potentially the most interesting are observations of antimitotic and antitumor activity of BoNT/A. However, the exact mechanisms require further studies.